D-Dimer Level with Cerebral Venous Sinus Thrombosis (CVST) Occurrence Using Digital Subtraction Angiography (DSA) - Afdi Arahim Putra; Eppy Buchori; Hilman Hilman; Lisda Amalia (Global Medical & Health Communication (GMHC), 2019)
Cerebral venous sinus thrombosis (CVST) is a cerebrovascular disease in the form of occlusion due to thrombus in the venous and cerebral sinuses. It rarely occurs and has varied clinical symptoms and radiological features and challenging to diagnose. D-dimer used as a diagnostic marker for cases of venous thromboembolism, with a sensitivity of around 90–92%. However, the specificity is not too high (70–73%) because it can also increase in other conditions. Digital subtraction angiography (DSA) is a gold standard examination to establish the diagnosis of CVST. The purpose of this study was to determine the relationship between the D-dimer level and CVST using DSA at Dr. Hasan Sadikin General Hospital in Bandung. This study used an observational analytic method with a case-control study design using retrospective data from medical records at Dr. Hasan Sadikin General Hospital in January 2017–August 2019. The research subjects divided into two groups, namely the high D-dimer levels and the normal/low D-dimer level. Forty people meet the inclusion criteria, ages averaging from 44.77±14.40 years, and consists of 9 male patients (22%) and 31 women patients (78%). For normal/low D-dimer levels 20 patients (50%) and high D-dimer levels 20 patients (50%). Statistical test results measuring D-dimer and CVST levels found a significant relationship (p<0.05). In conclusion, there is a relationship between D-dimer levels with CVST events that have been done by DSA. The higher the D-dimer level, the higher the suspicion of CVST. KADAR D-DIMER DENGAN KEJADIAN CEREBRAL VENOUS SINUS THROMBOSIS (CVST) MENGGUNAKAN DIGITAL SUBTRACTION ANGIOGRAPHY (DSA)Penyakit cerebral venous sinus thrombosis (CVST) merupakan penyakit serebrovaskular berupa oklusi akibat trombus di saluran vena dan sinus serebral yang jarang terjadi dengan gejala klinis dan gambaran radiologis yang bervariasi, serta sangat sulit untuk didiagnosis. D-dimer dapat dijadikan sebagai penanda diagnostik bagi kasus-kasus tromboembolisme vena dengan sensitivitas 90–92%, namun spesifisitasnya tidak terlalu tinggi (70–73%) karena dapat juga meningkat pada kondisi lain. Digital subtraction angiography (DSA) merupakan pemeriksaan baku emas untuk menegakkan diagnosis CVST. Tujuan penelitian ini mengetahui hubungan antara kadar D-dimer dan CVST menggunakan DSA di RSUP Dr. Hasan Sadikin Bandung. Penelitian ini merupakan observasional analitik dengan rancangan kasus kontrol menggunakan data retrospektif dari rekam medis di RSUP Dr. Hasan Sadikin Bandung pada bulan Januari 2017–Agustus 2019. Subjek penelitian dibagi menjadi 2 kelompok, yaitu kelompok D-dimer tinggi dan kelompok D-dimer normal/rendah. Hasil penelitian didapat 40 orang yang memenuhi kriteria inklusi, usia rerata 44,77±14,40 tahun yang terdiri atas pasien laki-laki 9 orang (22%) dan perempuan 31 orang (78%). Untuk kadar D-dimer kategori normal/rendah 20 orang (50%) dan tinggi 20 orang (50%). Hasil uji statistik mengukur kadar D-dimer dan CVST didapatkan hubungan yang bermakna (p<0.05). Simpulan, terdapat hubungan antara kadar D-dimer dan kejadian CVST yang telah dilakukan DSA. Semakin tinggi kadar D-dimer, semakin tinggi kecurigaan kejadian CVST.